5- months exposed implant after osteosynthesis is not necessarily a problem: A case report of a distal tibia fracture - Johanna Michel; Nermine Habib; Joseph M. Schwab; Angela Seidel (Trauma Case Reports)
Case: A 66-year-old patient sustained a closed tibial fracture which was treated by minimal invasive plate osteosynthesis. She developed a skin necrosis at the contusion side one month after surgery. A free gracilis flap was performed for soft tissue coverage together with hardware replacement. The intraoperative histopathological examen showed no signs of infection. One out of four positive intraoperative cultures taken from bone samples was positive and was interpreted as contamination. That is why the prophylactic antibiotic therapy with Cefuroxime was stopped after 5 days. The gracilis flap developed a distal necrosis with exposure of hardware. As there were no signs of active nor systematic infection no antibiotics were administrated. Directive wound healing was performed with the skin substitute Nushield® which took 5 months.After consolidation of the fracture, the plate was removed. Intraoperative cultures of bone samples during hardware removal, as well as sonication fluid culture of the plate, were negative. Conclusion: This case challenges the paradigm that exposed osteosynthesis hardware is always contaminated by cutaneous bacteria.